Engaging the theology of mission in rural ministry - Shafer, Travis L. (Covenant Theological Seminary, 2023)
1 online resource (ix, 149 leaves); Includes bibliographical references (leaves 145-149) ; Thesis (D. Min.)--Covenant Theological Seminary, 2023 ; Abstract